The Relevancy and Demand of Public Administration Today: The Case of Botswana - Balisi, S. (International Conference on Public Administration and Development Alternatives (IPADA), 2018)
This paper draws from a needs assessment survey for a Bachelor’s Degree in Public Administration that was carried out in Botswana during the academic year 2016/17. The main purpose of the survey was to determine the relevancy of a degree in Public Administration in Botswana through ascertaining its demand by prospective learners and the demand of graduates of the programme by prospective employers. The survey was prompted by a tertiary programme design process that requires development of programme proposal. One of the integral parts of that proposal is an empirically grounded justification of the programme demonstrating whether it is needed by the potential participants (prospective learners and employers) or not. Thus, specific objectives of the study centred on relevancy and the demand of the programme in Botswana. The survey targeted respondents employed by government ministries and departments at both central and local levels of government. It also included employees of local authorities and relevant parastatal organizations. Targeted respondents included junior officers, senior officers and top management officers holding administrative and management positions within these establishments. A total number of 109 respondents out of a total target of 150 respondents across the country were able to complete and return the study questionnaires. This was a cross-sectional study which used quantitative research approach. The survey results were analysed using the IBM Statistical Package for the Social Sciences (SPSS) software. The study found that a degree in Public Administration is relevant to Botswana due to a high demand for the programme by prospective learners in the country. In addition, the study found that there is moderate to high demand of Public Administration graduates by prospective employers in Botswana. Finally, the study recommended that a degree in Public Administration be introduced by the Botswana Open University.
Journal article published in the International Conference on Public Administration and Development Alternatives 04 - 06 July 2018, Stellenbosch University, Saldahna Bay, South Africa
Keywords: Botswana; Demand; Public Administration; Relevancy; Curriculum-based assessment; Education - Curricula; Curriculum evaluation - Botswana